FASHION AND BEAUTY PERSPEKTIF HUKUM ISLAM - Aliasyadi, Aliasyadi (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
Fashion and beauty is part of human nature. Islam called it as fitrah. But Islam sets the rules in the form of conditions that must be considered so that fashion and beauty does not become something contrary to Islamic law. This paper will answer 3 issues: how the history of beauty in human life, how the Islamic view of the development of fashion and beauty, and what are the conditions specified in Islam. This paper is a library research using a normative descriptive approach by examining the opinions of ulama and modern phenomena in human society.